The customer consequences of returns in online retailing: An empirical analysis - Griffis, Stanley E.; Rao, Shashank; Goldsby, Thomas J.; Niranjan, Tarikere T. (Journal of Operations Management, 2012)
AbstractPressure continues to build on the operations management function to facilitate system and firm level benefits. In the online marketplace, one area of growing interest is that of product returns. Though commonly viewed as a cost center from an operations perspective, operations’ actions have the potential to strongly influence future customer buying behavior in several ways. Using an archival database of actual purchase and returns history provided by a moderately sized online retailer, this study examines the relationship between a customer's experience of product returns, and subsequent shopping behavior. Employing transaction cost, consumer risk, and procedural justice theories, we demonstrate that the returns management process, rather than being regarded as an afterthought to the production and deployment of goods, can significantly and positively influence repurchase behavior. Additionally, we provide evidence that certain customers should be considered for prioritization in the returns process. We suggest ways through which operations managers can take care in discharging their responsibilities in this area – to make returns processing more than simply a “necessary cost of doing business” rather, using it to their advantage in engendering repeat and increased purchase behavior.